Tumor Control Probability Modeling for Radiation Therapy of Keratinocyte Carcinoma - Prior, Phillip; Awan, Musaddiq J.; Wilson, J Frank; Li, X. Allen (Frontiers in Oncology, 2021)
Background: Radiotherapy (RT) with electrons or photon beams is an excellent primary treatment option for for keratinocyte carcinoma (KC), particularly for non-surgical candidates. Our objective is to model tumor control probability (TCP) based on the pooled clinical data of primary basal & cutaneous squamous cell carcinomas (BCC & cSCC, respectively) in order to optimize treatment schemes. Methods: Published reports citing crude estimates of tumor control for primary KCs of the head by tumor size (diameter: <= 2 cm & > 2 cm) were considered in our study. A TCP model based on a sigmoidal function of biological effective dose (BED) was proposed. Three-parameter TCP models were generated for BCCs < 2 cm, BCCs > 2cm, cSCCs < 2 cm and cSCCs > 2 cm . Equivalent fractionation schemes were estimated based on the TCP model and appropriate parameters. Results: TCP model parameters for both BCC and cSCC for tumor sizes <= 2 cm and > 2cm were obtained. For BCC, the model parameters were found to be TD50 = 56.62 ± 6.18x10-3 Gy, k = 0.14 ± 2.31x10-2 Gy-1 and L = 0.97 ± 4.99x10-3 and TD50 = 55.78 ± 0.19 Gy, k = 1.53 ± 0.20 Gy-1 and L = 0.94 ± 3.72x10-3 for tumor sizes of < 2 cm & > 2 cm, respectively. For SCC the model parameters were found to be TD50 = 56.81 ± 19.40x104 Gy, k = 0.13 ± 7.92x104 Gy-1 and L = 0.96 ± 1.31x10-2 and TD50 = 58.44 ± 0.30 Gy, k = 2.30 ± 0.43 Gy-1 and L = 0.91± 1.22x10-2 for tumors <= 2cm & > 2 cm, respectively. The TCP model with the derived parameters predicts that radiation regimens with higher doses lead to higher TCP, especially for KCs > 2 cm in size. Conclusion: Four TCP models for primary KCs were developed based on pooled clinical data that may be used to further test the RT regimens from the 2020 ASTRO guidelines. Increasing both number of fractions & dose per fraction may have clinically significant effects on tumor control for tumors > 2 cm in size.